Impact of medication regimen simplification on medication adherence and clinical outcomes in patients with long-term medical conditions - Elnaem, Mohamed Hassan Abdelaziz; Irwan, Nor Afifah; Abubakar, Usman; Syed Sulaiman, Syed Azhar; Elrggal, Mahmoud E.; Cheema, Ejaz (Dove Medical Press, 2020)
Background: This study aims to identify interventions used to reduce medication regimen complexity and to assess their impact on medication adherence and clinical outcomes. Methods: A literature search was conducted using pre-defined search terms in three scientific databases, including ScienceDirect, ProQuest and MEDLINE. Original research articles published in English between 2009 and 2020 that assessed the impact of medication regimen simplification on medication adherence in patients with long-term medical conditions were eligible for inclusion. Review articles, meta-analysis studies and conference proceedings were excluded. Data charting was done in an iterative process using a study-specific extraction form. Results: Of the 684 studies identified through initial searches, 17 studies were included in the review. Nine studies involved simplification of medication regimen related to HIV, while three studies focused on patients with diabetes with or without coronary artery disease. The remaining five studies included medications used among elderly patients or medications related to hypertension, psychiatric disorders, glaucoma and kidney diseases. Three medication regimen simplification strategies were identified; fixed-dose combination (n = 7), once-daily dosing (n = 4) and the combination of both fixed-dose and once-daily dosing (n = 6). Overall, most of the regimen simplification strategies (14 out of 17) were found to be useful in improving medication adherence. There was no assessment of clinical outcomes in four out of 17 studies. Furthermore, more than half of the studies that assessed clinical outcomes did not show any additional impact on clinical outcomes. Conclusion: The findings suggest that there was an equal utilization of the three main approaches of regimen simplifications; fixed-dose combination, once-daily dosing and a combination of both. Overall, most of the regimen simplification strategies were found to be effective in improving medication adherence. However, the associated improvement in medication adherence did not extend to improvement in the clinical outcomes.